RISIKO HUKUM DALAM PRAKTIK PERGADAIAN SWASTA YANG TIDAK TERDAFTAR DI OTORITAS JASA KEUANGAN - Faradilla Cendana Galuh, - (2019)
In Indonesia, before the Regulation of Financial Services Authority, there are noregulations for the private pawnshops, therefore, the enactment of theseregulations, will impact the private pawnshops in Indonesia, one of them is the private pawnshops regulates and supervises in Indonesia. This research intendedto find out the weaknesses of the juridical aspects that cause legal risks in practiceprivate pawnshops that is not registered in the Financial Services Authority. Thisresearch uses a Combine Method of Normative Jurisdiction, this research is thelibrary research by using secondary data that consisting of three legal materials,that is the primary source, secondary source and tertiary source and generatedescriptive analytical data. Based on the deliberation of this research, legal riskscan occurs in all aspects of transactions in the private pawnshop that are notregistered or licensed, including the collateral to the collateral auctions. The legal risk happen becaused there is no regulation regarding the sanction for pawnshopsthat are not registered nor licensed, and the supervision by Financial ServicesAuthority only for the registered and licensed pawnshops. With the result that the pawn business service that are not registered or licensed they were only givensocialization or instructions about the Regulation of Financial Services Authority.